Beyond happiness: The three waves of positive psychology and the future of wellbeing - Gökmen Arslan (Journal of Happiness and Health, 2025)
This editorial explores the evolving landscape of positive psychology by tracing its development through three major waves and outlining emerging discussions toward a potential fourth. The first wave, launched in the late 1990s, emphasized individual strengths, positive emotions, and subjective wellbeing—largely shaped by Western epistemologies and dominated by quantitative, empirical methodologies. While foundational to the field, this wave has been critiqued for neglecting complexity, cultural diversity, and ethical concerns. In response, the second wave introduced a more dialectical understanding of wellbeing, integrating both positive and negative experiences and recognizing the transformative potential of adversity. This phase embraced contextual sensitivity, methodological pluralism, and cross-cultural considerations, fostering a more nuanced view of human flourishing. Building on these earlier developments, the third wave of positive psychology adopts a systems-level and interdisciplinary approach. It emphasizes interconnectedness, ecological and cultural contexts, spiritual dimensions, and social justice. This wave views wellbeing as a dynamic, relational, and ethically grounded phenomenon that transcends individual psychological states. Researchers increasingly engage in post-disciplinary collaborations, employing diverse methods to understand how flourishing unfolds across individuals, communities, and ecosystems. The editorial also highlights initial proposals for a fourth wave that aligns wellbeing science with global challenges such as sustainability, equity, and public health—framing flourishing as a shared responsibility in an interconnected world. Ultimately, this editorial calls for a reimagining of positive psychology as a science not just of personal happiness but of collective and sustainable wellbeing. By embracing complexity, humility, and global perspectives, future directions in the field can better serve the diverse needs of humanity and foster flourishing at both individual and societal levels.